1990
DOI: 10.1007/bf02102078
|View full text |Cite
|
Sign up to set email alerts
|

A maximum likelihood approach to the detection of selection from a phylogeny

Abstract: A large amount of information is contained within the phylogenetic relationships between species. In addition to their branching patterns it is also possible to examine other aspects of the biology of the species. The influence that deleterious selection might have is determined here. The likelihood of different phylogenies in the presence of selection is explored to determine the properties of such a likelihood surface. The calculation of likelihoods for a phylogeny in the presence and absence of selection, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…An unrooted phylogenetic tree was generated using FITCH (22) with the default parameters plus the additional options of randomizing the input order of sequences and global rearrangement optimization. The representative tree was produced using the MEGA 3.1 software package (33).…”
Section: Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%
“…An unrooted phylogenetic tree was generated using FITCH (22) with the default parameters plus the additional options of randomizing the input order of sequences and global rearrangement optimization. The representative tree was produced using the MEGA 3.1 software package (33).…”
Section: Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%
“…Second, for each position i in a regulatory site we assume there is a (generally unknown) set of four selection coefficients for the possible nucleotides at this position, which are constant through time and, in the limit of large time, lead to the set of equilibrium frequencies w ␣ i . Following Golding and Felsenstein (1990), Halpern and Bruno (1998) have shown that, in the weak mutation limit of the standard Kimura-Ohta theory, one can uniquely determine substitution rates in terms of the mutation rates and the equilibrium frequencies w ␣ i . In particular, if r ␣␤ i is the rate of substitution from ␤ to ␣ at position i, µ ␣␤ the rate of mutation from ␤ to ␣, and w ␣ i the equilibrium frequency of ␣ at this position, we have (Halpern and Bruno 1998) …”
Section: Evolutionary Modelmentioning
confidence: 99%
“…The sequence used for comparison is rat Kv3, except for human Kv3.4b. Analysis by the parsimony method was performed using the PROTPARS program in the Phylogeny Inference Package (Golding and Felsenstein, 1990). The Drosophila Shaw K ϩ channel was used as the outgroup.…”
Section: Resultsmentioning
confidence: 99%